Weak Emission Standards and Australia's Low Takeup of Electric Vehicles. Issue 4 (15th November 2022) - Martin, Peter
Abstract : Australia is unusual among developed countries both in lacking fleet‐wide vehicle carbon dioxide emission standards and in having a very low takeup of all‐electric vehicles. This paper outlines how fleet‐wide vehicle carbon dioxide emission standards operate and identifies mechanisms by which their absence might lead to a low takeup of electric vehicles in countries such as Australia. Although hard to verify one of those mechanisms in Australia (higher prices charged for all‐electric vehicles), it is easy to verify the unusually low number of models of all‐electric models made available for sale. The paper also outlines Australia's slow 15‐year journey towards standards, pointing to the possible role of political machinations and political caution in delaying their introduction. It identifies one group of employees with much to lose from a rapid uptake of electric vehicles—motor mechanics.